Estudio sobre las variables económicas del aguacate hass en Colombia como producto altamente atractivo para el mercado de exportación (2021)
In the present work, it will be possible to show the growth through the years that the hass type avocado has acquired, a process that has been growing rapidly due to the fact that it has been in the spotlight for a few years by different companies in our country as a product. highly attractive for a new economic alternative to it, demonstrate the competitiveness that our country has against the rest of the world and position this type of avocado in the best international markets. The processes and stages for the export of avocado and its different types that can be used for future negotiations for the benefit of any business were evidenced.